Neural tissue engineering: nanofiber‐hydrogel based composite scaffolds. (15th July 2015) - Shelke, Namdev B.; Lee, Paul; Anderson, Matthew; Mistry, Nikhil; Nagarale, Rajaram K.; Ma, Xin‐Ming; Yu, Xiaojun; Kumbar, Sangamesh G.
Abstract : Scaffolds used for soft tissue regeneration are designed to mimic the native extracellular matrix (ECM) structurally and provide adequate mechanical strength and degradation properties. Scaffold architecture, porosity, stiffness and presence of soluble factors have been shown to influence human mesenchymal stem cells (hMSCs) differentiation along neuronal lineage. The present manuscript evaluated the performance of a composite scaffold comprised of electrospun polycaprolactone (PCL) nanofiber lattice coated with sodium alginate (SA) for neural tissue engineering. The nanofiber lattice was included in the scaffold to provide tensile strength and retain suture thread on the nerve graft. Sodium alginate was used to control matrix hydrophilicity, material stiffness and controlled release of biological molecules. The effect of SA molecular weight on the composite scaffold tensile properties, hMSCs adhesion, proliferation and neurogenic differentiation was evaluated. Both random and aligned composite scaffolds showed significantly higher tensile properties as compared to PCL fiber matrix alone indicating the reinforcement of SA hydrogel into fiber lattice. Low molecular weight SA coating because of its low viscosity resulted in uniform penetration into the fiber lattice and resulted in significantly higher tensile strength as compared to high molecular weight SA. Both composite scaffolds showed a controlled SA erosion rate and lost >95% of the SA coating over a period of 10 days under in vitro conditions. Composite scaffolds showed progressive hMSCs growth over 14 days and resulted in significantly higher amount of DNA content (almost double on day 7 and 14) as compared to control PCL fiber matrices. Immunostaining experiments showed higher and uniform expression of the neurotropic protein S‐100 on composite scaffolds containing low molecular weight SA. These composite scaffolds may be suitable for peripheral nerve regeneration. Copyright © 2015 John Wiley & Sons, Ltd.